Experimental and numerical study of 7A04-T6 extruded aluminium alloy lipped angle columns in axial compression. (October 2022) - Xu, Zhaoyu; Tong, Genshu; Zhang, Lei; Guo, Yong
Abstract: The behaviour and design method of 7A04-T6 high-strength extruded aluminium alloy lipped angle columns in axial compression are investigated. First, compressive tests on 27 pin-ended lipped angle columns of various dimensions were conducted. Measurement on initial geometric imperfections and tensile coupon tests were also performed. Second, the finite element (FE) models were developed to simulate the compressive behaviour of the tested specimens. The validated FE models were then used to carry out a parametric study covering a wide range of cross-sectional dimensions and column slendernesses. The obtained ultimate compressive strengths were compared with existing design codes in Europe, China, America and Canada for aluminium alloy structures. Furthermore, the direct strength method (DSM) codified in AISI S100-16 was also considered. In predicting the ultimate compressive strength, the elastic global buckling stress was determined from classical column buckling theory, while the elastic sectional buckling stress was given by energy method. The comparisons show that the compressive strengths of columns failing in flexural buckling are generally well predicted by existing design methods. For torsional–flexural buckling, the Eurocode 9 (EC9) generally gives more accurate predictions and the other design rules are relatively conservative, because an independent strength curve is adopted in EC9 and the interaction with local buckling is excluded. Finally, modified equations are proposed to improve the accuracy of DSM in predicting the compressive capacities of columns failing in distortional buckling and torsional–flexural buckling. Highlights: 7A04-T6 high-strength aluminium alloy lipped angle columns were tested. An extensive parametric study was conducted using the validated finite element model. The obtained results were compared with four design codes and direct strength method. Modified strength curves were proposed to improve the accuracy of direct strength method.